Draft Annual Plan Proposals 2008-09 Government of Kerala - Planning Commission (Planning Commission, 2008)
The tenth plan period had witnessed a serious setback to the planning effort of the state. Plan expenditure as a proportion of GSDP, which was higher than the average for all states in 2002-03, the first year of the tenth plan, had fallen way below this average by 2006-07 (BE). In fact by the end of the tenth plan this ratio was the lowest among all South Indian states. And the average for the plan period as a whole was even lower than the state’s own figure for 1999-00. This had a particularly adverse impact on the social sectors, including education and health, where development expenditure as a proportion of GSDP was lower throughout the tenth plan period than it had been in 1999-00. And it had crippled the ability of the state to cope with the impact of the agrarian crisis, and more generally of the crisis of petty production, that had hit the state during the tenth plan years, resulting inter alia in a spate of peasant suicides.
Government of Kerala State Planning Board Thiruvananthapuram